Endocrine features of Prader-Willi syndrome: a narrative review focusing on genotype-phenotype correlation - Madeo, Simona F.; Zagaroli, Luca; Vandelli, Sara; Calcaterra, Valeria; Crinò, Antonino; De Sanctis, Luisa; Faienza, Maria Felicia; Fintini, Danilo; Guazzarotti, Laura; Licenziati, Maria Rosaria; Mozzillo, Enza; Pajno, Roberta; et al. (Frontiers in Endocrinology, 2024)
Prader-Willi syndrome (PWS) is a complex genetic disorder caused by three different types of molecular genetic abnormalities. The most common defect is a deletion on the paternal 15q11-q13 chromosome, which is seen in about 60% of individuals. The next most common abnormality is maternal disomy 15, found in around 35% of cases, and a defect in the imprinting center that controls the activity of certain genes on chromosome 15, seen in 1-3% of cases. Individuals with PWS typically experience issues with the hypothalamic-pituitary axis, leading to excessive hunger (hyperphagia), severe obesity, various endocrine disorders, and intellectual disability. Differences in physical and behavioral characteristics between patients with PWS due to deletion versus those with maternal disomy are discussed in literature. Patients with maternal disomy tend to have more frequent neurodevelopmental problems, such as autistic traits and behavioral issues, and generally have higher IQ levels compared to those with deletion of the critical PWS region. This has led us to review the pertinent literature to investigate the possibility of establishing connections between the genetic abnormalities and the endocrine disorders experienced by PWS patients, in order to develop more targeted diagnostic and treatment protocols. In this review, we will review the current state of clinical studies focusing on endocrine disorders in individuals with PWS patients, with a specific focus on the various genetic causes. We will look at topics such as neonatal anthropometry, thyroid issues, adrenal problems, hypogonadism, bone metabolism abnormalities, metabolic syndrome resulting from severe obesity caused by hyperphagia, deficiencies in the GH/IGF-1 axis, and the corresponding responses to treatment.